Edukasi Pembuatan Yoghurt Berbahan Dasar Susu Sapi Pada Ibu PKK Di Desa Kemuning Lor Kabupaten Jember - Yohan Yuanta; Veronika Vestine; Dina Fitriyah; Surya Dewi Puspita; Gandu Eko Julianto Suyoso; Bakhtiyar Hadi Prakoso (PEKAT: Jurnal Pengabdian Kepada Masyarakat, 2023)
Milk production for dairy cows in Jember Regency is quite a lot, marked by a total production per year reaching 2.9 million liters per/year, but the use of fresh milk into processed products in Rayap Hamlet, Kemuning Lor Village, Arjasa District is still lacking, only limited to being used as a dairy product. pure cow's milk drink. Fresh cow's milk that has not undergone processing is easily damaged and has low economic value. Therefore, efforts are needed to be able to increase the economic value, benefits and good shelf life of the processing of fresh milk, one of the processing based on fresh milk is to make yogurt. The nutritional content of yogurt, especially protein and calcium, can meet nutritional needs. Nutrition is needed in every life cycle, starting from the womb (fetus), infants, children, adults, and the elderly. This service is carried out to increase knowledge and skills through education on processing milk into yogurt. This activity involved PKK Kemuning Lor Village women and institutional components from tertiary institutions, namely lecturers as activity assistants and assisted by two students. The output achieved from this service is an increase in knowledge of making yogurt.